Kinetic or Thermodynamic Product? Case Studies on the Formation of Regioisomers of Tetraphenyladamantanes - Berking, Tim; Frey, Wolfgang; Richert, Clemens (Synthesis, 2023)
Tetraaryladamantanes (TAAs) with alkoxyphenyl groups are interesting synthetic targets because they can act as crystallization chaperones for liquid compounds. Their carbon framework is set up by Friedel–Crafts alkylation, using adamantane-1,3,5,7-tetraol and anisole derivatives as starting materials. One successful chaperone is 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro). This compound was initially considered the thermodynamic product of alkylation and its reaction towards strong Brønsted acid is reported. We now report that exposure of TBro to strong Brønsted acid leads to its regioisomer 1,3,5,7-tetrakis(4-bromo-2-methoxyphenyl)adamantane (iTBro) as the dominant product, obtained in a yield of 68%, far surpassing the 20% yield reported earlier for TBro. We also investigated the reactions of 3-iodo-, 3-chloro-, and 3-fluoroanisole to the corresponding TAAs and obtained yields of 66%, 26% and 52% for the main regioisomer. While 3-iodoanisole gave the same regioisomer as bromoanisole, 3-chloroanisole afforded complex mixtures and 3-fluoroanisole furnished 1,3,5,7-tetrakis(2-fluoro-4-methoxyphenyl)adamantane (TFM) in 52% yield as the main product. When mixtures of regioisomers were isomerized with an excess of triflic acid, the thermodynamic products were obtained in 76–91%. These results show how subtle effects govern the regioisomeric product distribution of aryladamantanes. They also help to make novel crystallization chaperones accessible in high yields.
Keywords: adamantane; alkylation; crystallization; Friedel–Crafts reactions; regioselectivity